Pelagios – Connecting Histories of Place. Part I: Methods and Tools. Issue 1 (October 2021) - Vitale, Valeria; Soto, Pau de; Simon, Rainer; Barker, Elton; Isaksen, Leif; Kahn, Rebecca
Abstract : This article provides a short history of the methods and tools developed by the Pelagios initiative: a series of seven projects dedicated to linking digital historical resources based on the geographic places to which they relate and refer. The first section of the article situates the work within the wider field of semantic and geospatial technologies. It then describes the initial development of the Pelagios methodology through an open consortium of ancient Mediterranean data resource providers, in association with the Pleiades Gazetteer of the Ancient World . The second section details how this approach was expanded for application in other historical and archaeological periods and domains, with a special focus on tool development. In particular, we reflect on the development and application of Recogito, an online semantic geoannotation platform that allows anyone to identify place references within historical texts, imagery or datasets.